Endothelial dysfunction in patients with metabolic syndrome: a prospective study in a rural institute in India - Zafar, Khwaja Saifullah; Singh, P. S.; Verma, Vijay Kumar; Wafai, N. A. (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to evaluate endothelial dysfunction in patients with metabolic syndrome. Methods: This prospective, cross-sectional, hospital based observational study included 45 patients with metabolic syndrome and 20 age and sex matched controls who attended hypertension clinic, diabetes clinic, general medicine OPD and patients admitted in wards department of medicine, UPRIMS&R, Saifai, Etawah, UP, India. All patients who fulfilled inclusion criteria were subjected to the color Doppler of the brachial artery in the department of radio-diagnosis of the same institute. Results: Of the 45 patients with metabolic syndrome included in the study, 22 patients (48.9%) were males and 23 patients (51.1%) were females. Ten males (45.5%) had a waist circumference of >90 cm whereas 20 females (87%) had waist circumference of >80 cm. 9 males (40.9%) had abnormal waist hip ratio whereas 22 females (95.7%) had abnormal waist hip ratio. 43 patients (95.6%) had a SBP >130 mm of Hg whereas 39 patients (86.7%) had a DBP >85 mm of Hg. 24 patients (53.3%) had impaired fasting blood sugar i.e. >100 mg/dl ,25 patients (55.6%) had a TGL level >150 mg/dl, and 9 males (40.0%) had HDL < 40 mg/dl whereas 18 females (78.3%) had HDL value < 50 mg/dl respectively. The mean brachial artery baseline diameter were 3.50 ± 0.39 mm in males and 3.25 ± 0.29 mm in females respectively, FMD percentage was 14.91 ± 3.56 in females and 14.53 ± 4.02 in males, and GTN mediated dilatation were 27.67 ± 9.83% in females and 27.62 ± 6.85% in males respectively. Conclusion: Estimation of Endothelial Dysfunction in patients at risk of developing full blown Metabolic Syndrome may predict the cardiovascular morbidity and mortality in these individuals even before fulfilling the 3/5 criteria of NCEP/ATP III Guidelines for the diagnosis of metabolic syndrome.